2020
DOI: 10.1016/j.coelec.2020.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Local electrochemical impedance spectroscopy: A window into heterogeneous interfaces

Abstract: The ability to probe surface reactivity on a local scale has led to new insight on the comprehension of the electrochemical reactivity in relation with the microstructure of the surface. Among the different techniques developed in recent years, local electrochemical impedance spectroscopy has the advantage of using a transient approach to locally characterize a stationary electrochemical system without the need to add any redox mediator in solution, which is a great advantage for the study of different systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…7 μm radius, compared to the tip radius of 100 nm. This discrepancy can originate from the displacement of the probe due to thermal drift at low frequencies or/and from the frequency dispersion of the electric field, as reported for local EIS-AFM measurements in the case of small counter electrodes , (vide infra).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…7 μm radius, compared to the tip radius of 100 nm. This discrepancy can originate from the displacement of the probe due to thermal drift at low frequencies or/and from the frequency dispersion of the electric field, as reported for local EIS-AFM measurements in the case of small counter electrodes , (vide infra).…”
Section: Resultsmentioning
confidence: 97%
“…Significant frequency dispersion can be detrimental for the quantification of the local properties of conductive interfaces . For impedance imaging, we thus used a single frequency (320 Hz), which was sufficiently low to be sensitive to the interfacial capacitance but high enough to speed up the analysis at each pixel to avoid thermal drift issues (SI, Figure S3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques have also been used to evaluate other transfer functions involving electrochemical systems such as thermal impedance spectroscopy, 153 electrohydrodynamic impedance [154][155][156] , modulation of the interfacial capacitance 157-160 and local electrochemical impedance spectroscopy. [161][162][163][164][165] [H2] FIELD-SPECIFIC LIMITATIONS…”
Section: [H1] Limitations and Optimizationsmentioning
confidence: 99%
“…Local electrochemical impedance mapping (LEIM) can give valuable information on the mechanism of corrosion on a controlled defect made on coated metal samples [49,67,68]. Previous studies have shown that for the correct detection of heterogeneities in solid/liquid interfaces by using local electrochemical impedance, it is necessary to select adequate input AC signal frequency and ranges of electrolyte conductivity [69,70].…”
Section: Local Electrochemical Impedance Mapping (Leim)mentioning
confidence: 99%